A high entropy doped layered lithium-rich manganese-based positive electrode material and preparation method thereof
By controlling the doped elements and coated carbon layers in the lithium-rich manganese-based positive electrode material, the problem of oxygen evolution at high voltage is solved, and its cycle stability and rate performance is significantly improved, and it has good commercial application prospects.
Patent Information
- Application Number
- CN202311821605.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-12-27
AI Technical Summary
The existing lithium-rich manganese-based positive electrode material excretes oxygen at high voltage, resulting in low efficiency of Coulomb, poor cycle stability and continuous voltage decay for the first time, limiting its commercialization process.
By controlling the types and amounts of doped elements, reducing lattice defects, and covering a uniform and dense carbon coating layer on the surface of the material to improve conductivity and stability, a high-entropy doped layered lithium-rich manganese-based cathode material is prepared.
The rate performance and cycle stability of lithium-rich manganese-based positive electrode material are significantly improved, and the cycle retention rate can reach 87%, extending the service life of the battery.
Smart Images

Figure CN117712339B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion battery materials, and in particular relates to a high-entropy doped layered lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art
[0002] At present, several commonly used positive electrode materials on the market include layered LiCoO2, ternary materials, high-nickel positive electrode materials, polyanion-type LiFePO4 and spinel-type LiMn2O4, etc., but they have low specific capacity (120-200mAh / g) and / or high cost, which is not conducive to the lightweight, long-range and more extensive promotion and application of electric vehicles. Seeking higher energy density and lower cost positive electrode materials has always been the goal of academia and industry. Lithium-rich manganese-based positive electrode materials have become a research hotspot in recent years because of their high specific capacity (more than 250mAh / g, even more than 300mAh / g) and low cost. However, it also has many disadvantages. For example, its oxygen evolution at high voltage will lead to low first coulomb efficiency (65%-80%), poor cycle stability and continuous voltage decay. At present, the commercialization process is slow.
[0003] In order to improve the above problems, researchers have made improvements by preparing high-entropy doped layered positive electrode materials, so that the cycle performance and rate performance of the positive electrode manganese-rich based positive electrode materials have been greatly improved. For example, patent application CN115513449A discloses a layered lithium-rich manganese-based high-entropy positive electrode material, which is constructed by doping at least 4 metal elements of Mg, Al, Si, Ca, Ti, V, Cr, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ru, Sn, Sb, Te, Ta, W and Ce into the lithium-rich manganese-based material to have a higher intralayer configurational entropy.
[0004] However, this method has the following defects: (1) During the high entropy doping process, there are interactions and repulsions between the doped metal elements, which easily lead to lattice defects, thus affecting ion hopping and diffusion; (2) The layered lithium-rich manganese-based positive electrode material has the disadvantages of relatively poor chemical and mechanical stability due to the easy loss of oxygen in the layered oxide in a highly deoxidized state and the easy change in volume during charging and discharging, which will lead to poor long-cycle performance and short service life of the manganese-rich positive electrode material. Summary of the invention
[0005] In order to solve the problems of poor cycle performance, rate performance, and low initial efficiency of existing lithium-rich manganese-based positive electrode materials, the present invention reduces the lattice defects formed by the lithium-rich manganese-based positive electrode materials by controlling the type and amount of doping elements, and coats a uniform and dense carbon coating layer on the surface of the lithium-rich manganese-based positive electrode materials to improve conductivity and stability. The final prepared lithium-rich manganese-based positive electrode materials have good electrochemical properties. The specific technical scheme of the present invention is:
[0006] In the first aspect, the present invention provides a high entropy doped layered lithium-rich manganese-based positive electrode material, the chemical formula of which is Li 1.2 Ni x Mn y O2M z / C, where x+y=0.79-0.8, z=0.01-0.1;
[0007] M is at least three of Mg, Al, Sc, Ti, V, Cr, Fe, Co, Cu, and Zn, and at least one of Nb, Mo, Ta, and W.
[0008] Nb, Mo, Ta and W are high-valent elements, and the production of intercrystalline oxygen ions can balance the oxygen released during the first charge. At least three of Mg, Al, Sc, Ti, V, Cr, Fe, Co, Cu and Zn can be mixed with high-valent elements to achieve high-entropy doping, which can further stabilize the oxygen ions in the lattice framework of the lithium-rich manganese positive electrode. At the same time, this cation mixing can enhance the electronic conductivity of the material and greatly reduce the lattice changes caused by the insertion and extraction of lithium ions, which is beneficial to the stability of the lithium-rich manganese-based positive electrode material, thereby improving the rate performance and cycle stability.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned high entropy doped layered lithium-rich manganese-based positive electrode material, comprising the following steps:
[0010] Step 1, mixing an aqueous solution of nickel salt and manganese salt with an aqueous solution of sodium carbonate to obtain a mixed solution, adjusting the pH of the mixed solution to 7.0-8.5, and washing, drying and ball milling to obtain a precipitate;
[0011] Step 2, then adding the salt solution of doped ions to the precipitate and maintaining the pH of the mixture unchanged, stirring to react, and obtaining a powder after sintering and ball milling;
[0012] Step 3, adding lithium carbonate and ion-doped oxide to the powder obtained in step 2, mixing and ball milling, and then sintering and pulverizing to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0013] Step 4: adding a carbon source to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball milling, and then calcining to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0014] Specifically, the drying in step 1 is vacuum drying, the vacuum drying temperature is 100 to 130° C., and the drying time is 20 to 48 hours;
[0015] Specifically, the concentration of the aqueous solution of nickel salt and manganese salt in step 1 is 1.5-2.5 mol / L, and the molar ratio of nickel salt to manganese salt in terms of Mn and Ni is 2.5-3.5:1;
[0016] More specifically, the nickel salt is selected from at least one of nickel nitrate and nickel sulfate, and the manganese salt is selected from at least one of manganese nitrate and nickel nitrate;
[0017] Specifically, the concentration of sodium carbonate in the aqueous ammonia solution of sodium carbonate (Na2CO3) in step 1 is 2.5-3.5 mol / L, and the molar ratio of Na2CO3 to NH4OH is 3-5:1;
[0018] Specifically, the reaction time in step 2 is 16 to 24 hours;
[0019] Specifically, the concentration of the doping ion salt solution in step 2 is 0.1 to 0.15 mol / L;
[0020] Specifically, the doped ions in the ion-doped salt solution in step 2 and the ion-doped oxide in step 3 are at least three of Mg, Al, Sc, Ti, V, Cr, Fe, Co, Cu, and Zn and at least one of Nb, Mo, Ta, and W. In addition, the addition of the doped ion oxide can improve the stability of the structure of the lithium-rich manganese-based positive electrode material, help improve the failure mechanism of the lithium-rich manganese-based positive electrode material, and extend the service life of the battery.
[0021] More specifically, the ion-doped salt solution is a nitrate or sulfate solution of doped ions;
[0022] Specifically, the molar amount of the doped ions in the ion-doped salt solution and the ion-doped oxide is the same, which means that the added molar ratio of each doped ion in the ion-doped salt solution is the same; the added molar amount of each doped ion in the ion-doped oxide is the same.
[0023] More specifically, the washing reagent in step 1 includes but is not limited to water;
[0024] Specifically, the sintering in step 2 is high temperature sintering, and the specific process is:
[0025] First, heat the temperature to 430-480°C at a rate of 3-6°C / min and keep it for 5-7 hours, then heat the temperature to 800°C at a rate of 2-4°C / min and keep it for 12 hours, and finally cool it down to room temperature at a rate of 4-6°C / min.
[0026] Specifically, the molar ratio of the powder to lithium carbonate (Li2CO3) in step 3 is 1:1 to 1.1;
[0027] Specifically, the size of the high entropy doped lithium-rich manganese-based positive electrode material powder in step 3 is ≤5 μm; controlling the size in this step is more conducive to achieving uniform and dense coating of the organic carbon source;
[0028] Specifically, the sintering temperature in step 3 and the calcining temperature in step 4 are both 400-600° C., and the calcining time is both 6-10 hours;
[0029] Specifically, the carbon source in step 4 is a soluble organic carbon source, and the soluble organic carbon source is selected from at least one of glucose, ascorbic acid or tea polyphenols;
[0030] Specifically, the mass of the carbon source added in step 4 is 2.5-6% of the mass of the high-entropy doped layered lithium-rich manganese-based positive electrode material powder in step 3.
[0031] The technical solution of the present invention has the following beneficial effects:
[0032] The present invention realizes high entropy doping by doping four or more cations, thereby improving the rate performance and cycle performance of the lithium-rich manganese-based positive electrode material; by controlling the type, addition ratio and addition amount of the doping elements, the lattice defects formed in the preparation process of the lithium-rich manganese-based positive electrode material are reduced, and the structural stability and long-cycle stability of the lithium-rich manganese-based positive electrode material are improved; and a uniform and dense carbon coating layer is coated on the surface of the lithium-rich manganese-based positive electrode material to improve the conductivity and structural stability; the finally prepared lithium-rich manganese-based positive electrode material has good cycle performance and better rate performance, and even under a long cycle of 500 cycles, the cycle retention rate can reach 87%; in addition, the method of the present invention is simple and easy to operate, and has good commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The first cycle charge and discharge curves of the lithium-rich manganese-based positive electrode materials prepared in Example 1 and Comparative Example 1;
[0034] Figure 2 The first cycle charge and discharge curves of the lithium-rich manganese-based positive electrode materials prepared in Example 2 and Comparative Example 2;
[0035] Figure 3 The highest capacity charge and discharge curves of the lithium-rich manganese-based positive electrode materials prepared in Example 2 and Comparative Example 2. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0037] Example 1
[0038] Step 1, taking 2M nickel sulfate, manganese sulfate aqueous solution (the molar ratio of Mn to Ni is 3:1) and 3 mol / L sodium carbonate ammonia solution (the molar ratio of Na2CO3 to NH4OH is 4:1) and mixing to obtain a mixed solution, adjusting the pH of the mixed solution to 7.7, washing with water, vacuum drying at 115°C for 34h and ball milling to obtain a precipitate;
[0039] Step 2, then add 0.13 mol / L ferric nitrate, titanium nitrate and cobalt nitrate solutions according to the element ratio of Ni to Fe, Ti and Co of 57:1:1:1 and maintain the pH of the mixed solution unchanged, stir and react for 20 hours, first increase the temperature to 450°C at a heating rate of 4.5°C / min and keep it for 6 hours, then increase the temperature to 800°C at a heating rate of 3°C / min and keep it for 12 hours, finally cool it to room temperature at a cooling rate of 5°C / min, and obtain powder after ball milling;
[0040] Step 3, lithium carbonate is added to the powder obtained in step 2 at a molar ratio of precipitate to lithium carbonate (Li2CO3) of 1:1.05, molybdenum oxide and tungsten oxide are added at a molar ratio of Fe, Ti, Co to Mo, W in a solution of ferric nitrate, titanium nitrate and cobalt nitrate of 1:1:1:1, the mixture is ball-milled, and then sintered (400°C, 4h) and pulverized (<5μm) to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0041] Step 4: Add a carbon source according to 4% of the mass of the positive electrode material powder to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball mill, and then calcine at 500° C. for 6 hours to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0042] Comparative Example 1
[0043] Step 1, taking 2M nickel sulfate, manganese sulfate aqueous solution (the molar ratio of Mn to Ni is 3:1) and 3 mol / L sodium carbonate ammonia solution (the molar ratio of Na2CO3 to NH4OH is 4:1) and mixing to obtain a mixed solution, adjusting the pH of the mixed solution to 7.7, washing with water, vacuum drying at 115°C for 34h and ball milling to obtain a precipitate;
[0044] Step 2, adding lithium carbonate to the precipitate obtained in step 1 at a molar ratio of precipitate to lithium carbonate (Li2CO3) of 1:1.05, mixing and ball milling, and then sintering (400°C, 4h) and pulverizing (<5μm) to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0045] Step 3: Add 4% of the mass of the high entropy doped layered lithium-rich manganese-based positive electrode material powder into the carbon source for ball milling, and then calcine at 500° C. for 6 h to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0046] Example 2
[0047] Step 1, taking 2M nickel nitrate, manganese nitrate aqueous solution (the molar ratio of Mn to Ni is 3:1) and 3 mol / L sodium carbonate ammonia solution (the molar ratio of Na2CO3 to NH4OH is 4:1) and mixing to obtain a mixed solution, adjusting the pH of the mixed solution to 7.7, washing with water, vacuum drying at 115°C for 34h and ball milling to obtain a precipitate;
[0048] Step 2, then add 0.13 mol / L scandium sulfate, vanadium sulfate, iron sulfate and titanium nitrate solution according to the element ratio of Ni to Sc, V, Fe and Ti of 57:1:1:1:1 and maintain the pH of the mixed solution unchanged, stir and react for 20 hours, first increase the temperature to 450°C at a heating rate of 4.5°C / min and keep it for 6 hours, then increase the temperature to 800°C at a heating rate of 3°C / min and keep it for 12 hours, finally cool it to room temperature at a cooling rate of 5°C / min, and obtain powder after ball milling;
[0049] Step 3, lithium carbonate is added to the powder obtained in step 2 at a molar ratio of 1:1.05 between the precipitate and lithium carbonate (Li2CO3), tungsten oxide is added to the solution of scandium sulfate, vanadium sulfate, iron sulfate and titanium nitrate at a molar ratio of Sc, V, Fe, Ti and W of 1:1:1:1:1, the mixture is ball-milled, and then sintered (600°C, 3h) and pulverized (<3μm) to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0050] Step 4: Add a carbon source according to 4% of the mass of the positive electrode material powder to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball mill, and then calcine at 500° C. for 6 hours to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0051] Comparative Example 2
[0052] Step 1, taking 2M nickel nitrate, manganese nitrate aqueous solution (the molar ratio of Mn to Ni is 3:1) and 3 mol / L sodium carbonate ammonia solution (the molar ratio of Na2CO3 to NH4OH is 4:1) and mixing to obtain a mixed solution, adjusting the pH of the mixed solution to 7.7, washing with water, vacuum drying at 115°C for 34h and ball milling to obtain a precipitate;
[0053] Step 2, then add 0.13 mol / L scandium sulfate, vanadium sulfate, iron sulfate and titanium nitrate solution according to the element ratio of Ni to Sc, V, Fe and Ti of 57:1:1:1:1 and maintain the pH of the mixed solution unchanged, stir and react for 20 hours, first increase the temperature to 450°C at a heating rate of 4.5°C / min and keep it for 6 hours, then increase the temperature to 800°C at a heating rate of 3°C / min and keep it for 12 hours, finally cool it to room temperature at a cooling rate of 5°C / min, and obtain powder after ball milling;
[0054] Step 3, adding lithium carbonate to the powder obtained in step 2 at a molar ratio of precipitate to lithium carbonate (Li2CO3) of 1:1.05, and then sintering (600°C, 3h) and pulverizing (<3μm) to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0055] Step 4: Add a carbon source according to 4% of the mass of the positive electrode material powder to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball mill, and then calcine at 500° C. for 6 hours to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0056] Example 3
[0057] Step 1, mixing 1.5M aqueous solution of nickel nitrate and manganese sulfate (the molar ratio of Mn to Ni is 2.5:1) and 2.5mol / L aqueous solution of sodium carbonate (the molar ratio of Na2CO3 to NH4OH is 3:1) to obtain a mixed solution, adjusting the pH of the mixed solution to 7.0, washing with water, vacuum drying at 100°C for 20h and ball milling to obtain a precipitate;
[0058] Step 2, then add 0.1 mol / L titanium nitrate, chromium nitrate and cobalt nitrate solutions according to the element ratio of Ni to Ti, Cr and Co of 57:1:1:1 and maintain the pH of the mixed solution unchanged, stir and react for 16 hours, first increase the temperature to 430°C at a heating rate of 3°C / min and keep it for 5 hours, then increase the temperature to 800°C at a heating rate of 2°C / min and keep it for 12 hours, finally cool it to room temperature at a cooling rate of 4°C / min, and obtain powder after ball milling;
[0059] Step 3, lithium carbonate is added to the powder obtained in step 2 at a molar ratio of 1:1 between the precipitate and lithium carbonate (Li2CO3), and molybdenum oxide and tungsten oxide are added at a molar ratio of 1:1:1:1:1 between Ti, Cr, Co and Mo, W in a solution of titanium nitrate, chromium nitrate and cobalt nitrate, and the mixture is ball-milled, and then sintered (600°C, 4h) and pulverized (<3μm) to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0060] Step 4: Add a carbon source according to 2.5% of the mass of the positive electrode material powder to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball mill, and then calcine at 400° C. for 4 hours to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0061] Comparative Example 3
[0062] Step 1, mixing 1.5M aqueous solution of nickel nitrate and manganese sulfate (the molar ratio of Mn to Ni is 2.5:1) and 2.5mol / L aqueous solution of sodium carbonate (the molar ratio of Na2CO3 to NH4OH is 3:1) to obtain a mixed solution, adjusting the pH of the mixed solution to 7.0, washing with water, vacuum drying at 100°C for 20h and ball milling to obtain a precipitate;
[0063] Step 2, then add 0.1 mol / L titanium nitrate and chromium nitrate solution according to the ratio of Ni to Ti and Cr elements of 57:1:1 and maintain the pH of the mixed solution unchanged, stir and react for 16 hours, first increase the temperature to 430°C at a heating rate of 3°C / min and keep it for 5 hours, then increase the temperature to 800°C at a heating rate of 2°C / min and keep it for 12 hours, finally cool it to room temperature at a cooling rate of 4°C / min, and obtain powder after ball milling;
[0064] Step 3, lithium carbonate is added to the powder obtained in step 2 at a molar ratio of 1:1 between the precipitate and lithium carbonate (Li2CO3), molybdenum oxide is added to the solution of titanium nitrate and chromium nitrate at a molar ratio of 1:1:1 between Ti, Cr and Mo, and the mixture is ball-milled, and then sintered (600°C, 4h) and pulverized (<3μm) to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0065] Step 4: Add a carbon source according to 2.5% of the mass of the positive electrode material powder to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball mill, and then calcine at 400° C. for 4 hours to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0066] Example 4
[0067] Step 1, mixing 2.5M aqueous solution of nickel nitrate and manganese sulfate (the molar ratio of Mn to Ni is 3.5:1) and 3.5mol / L aqueous solution of sodium carbonate (the molar ratio of Na2CO3 to NH4OH is 5:1) to obtain a mixed solution, adjusting the pH of the mixed solution to 8.5, washing with water, vacuum drying at 130°C for 48h and ball milling to obtain a precipitate;
[0068] Step 2, then add 0.15 mol / L titanium nitrate, chromium nitrate and cobalt nitrate solutions according to the element ratio of Ni to Ti, Cr and Co of 57:1:1:1 and maintain the pH of the mixed solution unchanged, stir and react for 24 hours, first increase the temperature to 480°C at a heating rate of 6°C / min and keep it for 7 hours, then increase the temperature to 800°C at a heating rate of 4°C / min and keep it for 12 hours, finally cool it to room temperature at a cooling rate of 6°C / min, and obtain powder after ball milling;
[0069] Step 3, lithium carbonate is added to the powder obtained in step 2 at a molar ratio of 1:1.1 between the precipitate and lithium carbonate (Li2CO3), and molybdenum oxide and tungsten oxide are added to the solution of titanium nitrate, chromium nitrate and cobalt nitrate at a molar ratio of 1:1:1:1:1 between Ti, Cr, Co and Mo, W, and the mixture is ball-milled, and then sintered (600°C, 4h) and pulverized (<3μm) to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder;
[0070] Step 4: Add a carbon source according to 6% of the mass of the positive electrode material powder to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball mill, and then calcine at 600° C. for 6 hours to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
[0071] The capacity retention rate of the lithium-rich manganese-based positive electrode materials prepared in the examples and comparative examples after 500 cycles was tested, specifically the capacity retention rate after 500 cycles under 1C conditions. The test results are shown in
[0072] Table 1.
[0073] Test items Example 1 Comparative Example 1 Example 2 Comparative Example 2 Example 3 Comparative Example 3 Example 4 500 cycles capacity retention rate (%) 87 71 84 75 81 78 82
[0074] Depend on Figures 1 to 3 It can be seen from the test results in Table 1 that the high-entropy doped layered lithium-rich manganese-based positive electrode material prepared by the method of the present invention has good electrochemical properties, and the capacity retention rate is still high even under a long cycle of 500 cycles; no doping was performed in Comparative Example 1, no high-priced doping elements (Nb, Mo, Ta and W) were used in Comparative Example 2, and the types of doping elements in Comparative Example 3 were relatively small. The long-cycle capacity retention rate of the layered lithium-rich manganese-based positive electrode material finally prepared was low, and the electrochemical performance was relatively poor.
Claims
1. A high entropy doped layered lithium-rich manganese-based positive electrode material, characterized in that: Its chemical formula is Li 1.2 Ni x Mn y O2M z / C; wherein x+y=0.79-0.8, z=0.01-0.1; M is at least three of Mg, Al, Sc, Ti, V, Cr, Fe, Co, Cu and Zn and at least one of Nb, Mo, Ta and W; The high entropy doped layered lithium-rich manganese-based positive electrode material is prepared by the following preparation method: Step 1, mixing an aqueous solution of nickel salt and manganese salt with an aqueous solution of sodium carbonate to obtain a mixed solution, adjusting the pH of the mixed solution to 7.0-8.5, and washing, drying and ball milling to obtain a precipitate; Step 2, then adding a salt solution of doped ions to the obtained precipitate while maintaining the pH of the mixture unchanged, stirring to react, and obtaining a powder after sintering and ball milling; Step 3, adding lithium carbonate and ion-doped oxide to the powder obtained in step 2, mixing and ball milling, and then sintering and pulverizing to obtain a high-entropy doped layered lithium-rich manganese-based positive electrode material powder; wherein the molar amount of the doped ions in the ion-doped salt solution and the ion-doped oxide is the same; Step 4: adding a carbon source to the high entropy doped layered lithium-rich manganese-based positive electrode material powder, ball milling, and then calcining to obtain the high entropy doped layered lithium-rich manganese-based positive electrode material.
2. The high entropy doped layered lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The concentration of the aqueous solution of nickel salt and manganese salt in step 1 is 1.5-2.5 mol / L, and the molar ratio of nickel salt to manganese salt in terms of Mn and Ni is 2.5-3.5:
1.
3. The high entropy doped layered lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The nickel salt is selected from at least one of nickel nitrate and nickel sulfate, and the manganese salt is selected from at least one of manganese nitrate and manganese sulfate.
4. The high entropy doped layered lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The concentration of sodium carbonate in the aqueous ammonia solution of sodium carbonate in step 1 is 2.5-3.5 mol / L, and the molar ratio of sodium carbonate to NH4OH is 3-5:
1.
5. The high entropy doped layered lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The concentration of the salt solution of the doped ions in step 2 is 0.1 to 0.15 mol / L.
6. The high entropy doped layered lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The carbon source in step 4 is a soluble organic carbon source, and the soluble organic carbon source is selected from at least one of glucose, ascorbic acid or tea polyphenols.
7. The high entropy doped layered lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The mass of the carbon source added in step 4 is 2.5-6% of the mass of the high-entropy doped layered lithium-rich manganese-based positive electrode material powder in step 3.
Citation Information
Patent Citations
Layered lithium-rich manganese-based high-entropy positive electrode material, preparation method thereof and battery
CN115513449A
High-entropy oxide positive electrode material and preparation method and application thereof
CN115010190A
Medium-high entropy layered lithium-rich positive electrode oxide and preparation method thereof
CN115566186A